Macroeconomic effect of COVID-19 on West African Monetary Zone (WAMZ): A fan chart probability forecast analysis - Ngozi Eunice Egbuna; Augustine Ujunwa; Nathan Pelesai Audu (West African Journal of Monetary and Economic Integration, 2020)
The outbreak of COVID-19 pandemic presents an unprecedented and synchronized disruption of the economies of the West African Monetary Zone (WAMZ). This study uses the Conditional Fan Chart based on Vector Error Correction Model (VECM) to forecast the effects of the pandemic on three key macroeconomic variables that include consumer price index, gross domestic product, and external reserves. Annualized data spanning from 2000Q1 to 2020Q2 were used to forecast the macroeconomic effects of COVID-19 on the economies of WAMZ Member States from 2020Q3 to 2022Q4. The result forecast general deterioration in the selected macroeconomic variables. The pessimistic scenario further reveals that heightened uncertainty, the prominence of downside side risks from the second wave will worsen economic conditions in the WAMZ.
Keywords: C01; E65; F45; F62; 330; COVID-19; Macroeconomic Effect; Fan chart; WAMZ